Aggressive osteoblastoma in the Maxilla: Unusual lesion in the craniofacial skeleton - Salmen, Fued Samir [UNESP]; Oliveira, Marina Reis [UNESP]; Navarro, Cláudia Maria [UNESP]; Dedivitis, Rogério Aparecido [UNESP]; Filho, Valfrido Antonio Pereira [UNESP]; Gabrielli, Mario Francisco Real [UNESP] (Wolters Kluwer, 2017)
Osteoblastomas are benign bone tumors, which are unusual in the craniofacial skeleton, being most often observed in the axial skeleton and long bones. The most common site in the maxillofacial region is the mandible and the involvement of the maxilla and paranasal sinuses is extremely rare. Although it is a benign lesion, the aggressive variant raises concerns due to its huge local destructive potential and tendency to relapse. In this clinical case, an aggressive osteoblastoma is described in a 7-year-old patient. The lesion was large and fully involved the left maxilla, including the maxillary sinus and the nasal cavity. Recurrent volume increase was observed 2 months following enucleation of the lesion and en bloc resection of the maxillary segment was performed. Histological and immunohistochemical evaluation associated with clinical and imaging findings allowed to define the tumor as an aggressive variant of osteoblastoma and not osteosarcoma, despite the aggressive behavior. The patient recovered well and no relapses were observed after 12 months following maxillary resection.
Keywords: Aggressive osteoblastoma; Bone tumors; Maxilla; Osteoblastoma